2013
DOI: 10.1080/02678292.2013.828332
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric study ofn-octyloxy-cyanobiphenyl (8OCB)

Abstract: Volumetric measurements were carried out on n-octyloxy-cyanobiphenyl (8OCB) over temperatures from ambient to 150• C at pressures up to 200 MPa, encompassing the liquid, nematic and smectic liquid crystalline, and crystal states. From the step changes in volume at the transitions, the phase boundaries and the associated activation enthalpies and energies were determined. The results are consistent with prior studies that were limited to a narrower range of thermodynamic conditions. The thermodynamic potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…From eq 3, using the gas phase dipole moments, the density (ρ = 0.98 g/cm 3 ) 24 and the measured ε S ′(T) we obtain g ∼ 0.36 within the isotropic phase of 8CB and 8OCB. The complete g(T) dependence in the isotropic phases of 8CB and 8OCB is provided in the Supporting Information (Figure S3).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…From eq 3, using the gas phase dipole moments, the density (ρ = 0.98 g/cm 3 ) 24 and the measured ε S ′(T) we obtain g ∼ 0.36 within the isotropic phase of 8CB and 8OCB. The complete g(T) dependence in the isotropic phases of 8CB and 8OCB is provided in the Supporting Information (Figure S3).…”
Section: Resultsmentioning
confidence: 91%
“…As we will see below this structural modification alters the phase diagram and stabilizes the same liquid crystalline phases to higher temperatures as compared to 8CB. The bulk thermodynamics and dynamics of 8OCB were studied with pressure-volume-temperature ( PVT ), DSC, , and DS, respectively. A single study reported on the effect of confinement (inside an aerosol matrix) on the dynamics by proton spin–lattice relaxation rate measurements in its nematic and smectic phases.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the dielectric relaxation spectra yield solely the low frequency relaxation time connected with the flip-flop molecular motions in a given LC phase (N for 7CB, 7PCH, 8PCH and 8OCB, Cr E for 6BT and 8BT). It should be added that the compounds with the CN group show a tendency to forming antiparallel doublets in the LC phases 50 The experimental dielectric and pVT data examined by us herein have been earlier measured and reported for the nematic phase of 7CB 51 52 , 7PCH 53 54 , 8PCH 55 56 , and 8OCB 18 57 as well as the crystalline E phase of 6BT 58 59 and 8BT 60 61 .…”
Section: Resultsmentioning
confidence: 61%
“…Unfortunately, the theoretical basis for discussion of the dynamic properties of molecules in LC phases is rather poor, in contrast to GFs. Therefore, our analyses of the thermodynamic aspects of the τ || (pVT) behaviors have been based on the power density scaling (PDS) law, which was originally formulated for GF systems and successfully verified for many material groups of GFs, but also satisfactorily applied to describe the thermodynamic evolution of the longitudinal relaxation times of various LC systems in different LC phases 3 6 14 15 16 17 18 19 . In this context, it is worth noting that there are two significant differences between the LC and GF systems: (i) the range of T and p in which a LC phase is thermodynamically stable is rather limited, in comparison with the supercooled regime of GF systems; (ii) there is no experimental evidence for non-Arrhenius temperature-dependences of τ || within LC phases, whereas such behavior is a common feature of GF substances.…”
mentioning
confidence: 99%
See 1 more Smart Citation